Autism Spectrum E-Learning Platform for Skill Enhancement and Support - Zulaffendi, Nur Alya Qistina; Hamzah, Mohd Hamdi Irwan (Applied Information Technology And Computer Science, 2024)
Autism is a widely known neurodevelopment disorder causes by differences in the brain. People with autism often struggle interacting with others, understanding their surrounding and has a different ways of learning from most people. Each autistic person is unique and have their own ways of absorbing new information which makes it difficult to determine the right method for their learning process. Parents especially those with no experience dealing with autistic child takes time to fully understand their child needs specifically in education. Therefore, this project proposes a digital learning portal for autism to support their learning process and provides platform for parents and their child to engage, learn, and gain knowledge in a safe environment. This portal is developed using a structured approach while utilizing a prototyping model. A software, Visual studio code plays an important role in implementing codes which is HTML, PHP and JavaScript whereas CSS are used to develop the design of the portal. The system is expected to help parents by providing the solution through multiple modules for parents, children and specialist in finding the best learning strategy and material for their autistic children to help them gained new knowledge and skills as well as keeping track of their progress and development.